The Aporia of Praxis: Materialist Aesthetics, the Avant-Garde, and Socially Engaged Art - Dias, Tobias (The Nordic Journal of Aesthetics, 2025)
Rather than discuss why the avant-garde remains a central point of reference for discussing the politics of art, this article addresses the philosophical and methodological problems involved in making the very conceptual construction of the “avant-garde.” Departing from a reconstruction of two prominent attempts to develop a “materialist aesthetics” in the 1970s, based on the historical experiences of the avant-gardes—Peter Gorsen and Peter Bürger—it turns to recent writings on “art activism” and “socially engaged art.” Examining how exemplary texts of the “social turn” are conditioned by a return to the avant-gardes, the aim here is to retrieve certain materialist coordinates whose necessity for critical thought has become apparent in recent writings. What is striking in many recent attempts to interpret new socially engaged and activist trends as manifestations of a new radical art praxis—or even as embodiments of a new “avant-garde”—is an avoidance of the problem of social mediation and an insufficient attention to historical periodization. This often leads to a hyperbolic and misconstrued notion of artistic agency and praxis, or, even worse, an aestheticized grammar of political struggle and insurrection. Against this backdrop, the article demonstrates that a materialist aesthetics must continue to engage with art’s aporetic relationship to praxis under capitalism. In this context, there is no reason to await a new avant-garde but every reason to look for attempts to actualize its self-negation—a self-negation that now falls to others to fulfill.